Ultrasonographic Assessment of Submandibular Salivary Gland at a Tertiary Care Centre in Nepal - Basnet, Prabhat; Singh, Ashutosh Kumar; Uphadhayay, Hari Prasad; Amgain, Kapil; Chaulagain, Rajib (Journal of Karnali Academy of Health Sciences, 2023)
Background: Various disease conditions can lead to the increased size of the submandibular gland. Normal dimensions of the salivary gland are useful for the identification and diagnosis of various associated pathology. The study objective was to assess the normal dimension of the submandibular gland using an ultrasonograph at a tertiary care centre in Nepal. Methods: The descriptive cross-sectional study was conducted in the Department of Radiology and Imaging College of Medical Sciences, Bharatpur, Nepal among 126 patients. Ultrasound of the submandibular gland was done of all patients with Toshiba Aplio 500 superficial probe. The data were collected and entered into Statistical Package for the Social Sciences version 16 and analyzed using descriptive statistics. Later the data was presented in form of tables. Results: There were in total 126 patients who participated in the study. Among them 78 (61.9%) were females and the rest were males. The mediolateral width of the right submandibular salivary gland (2.70±0.40 cms) was slightly greater than the left side. The volume of the left salivary gland (6.91±2.32 cm3) was slightly larger than the right side in males. However, there was no statistically significant difference between male and female Conclusion: This study concluded that the volume of the left salivary gland was slightly larger than the right side. The volume of the salivary gland of females was more than males.